RIGHTS AWARENESS AND THE LIVELIHOOD OF REFUGEES IN KYAKA II REFUGEE CAMP IN KYEGEGWA DISTRICT-UGANDA, A CROSS-SECTIONAL STUDY. - Katamba , Wycliff; Kamara, Ssemudu Julius (Student’s Journal of Health Research Africa, 2023)
Introduction; The study looked at the relationship between refugee rights awareness and their livelihood in Uganda using the Kyaka II Refugee Camp in Kyegegwa district. The study was conducted with three specific objectives; that is; to find out whether awareness of the right to work has a bearing on the livelihood of refugees in Kyaka II Refugee Camp. The study reviewed literature according to themes that were delivered from the objectives. Methodology; The study adopted both descriptive and cross-sectional research on a sample size of 402 and used questionnaires. Findings; Findings on awareness of the right to work revealed that the majority 58.6% of the respondents were not aware of that right as an entitlement, while 41.4% were aware. Findings on awareness of the right to own land property revealed that the majority 63.6% of the respondents were not aware that owning land was a right while 36.4% were aware. Recommendation; The government, with the support of donors and international actors, should establish a better conjuncture between rights, law, and economic interests related to refugees’ rights to work and access to labor markets, and also better align law and policy to give effect to the right to work thereby improving the livelihood of refugees.